Carbene - Saha, Satyen; Manna, Arunava (IntechOpen, 2022)
Carbenes are important molecules in chemistry because of their photochemistry and high reactivity. They have many potential applications in medicinal and materials chemistry. This book provides a comprehensive introduction to carbenes and discusses their characteristics, structure, and synthesis procedures. It gives special emphasis to N-heterocyclic carbenes (NHCs) and their metal complexes.